2006
DOI: 10.1073/pnas.0511302103
|View full text |Cite
|
Sign up to set email alerts
|

Between-subject transfer of emotional information evokes specific pattern of amygdala activation

Abstract: Emotional states displayed by an animal or a human can seriously affect behavior of their conspecifics. The amygdala plays a crucial role in the processing of emotions. In this study, we describe an experimental rat model of between-subject transfer of emotional information and its effects on activation of the amygdala. The rats were kept in pairs, and one animal (designated as ''demonstrator'') was treated to specific behavioral training of either foot-shockreinforced context conditioning or just exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
123
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(139 citation statements)
references
References 33 publications
10
123
1
1
Order By: Relevance
“…Our data show robust infant amygdala activation during the social transmission of fear (2-DG, c-Fos) consistent with adult social fear learning data (18,25). To determine if the amygdala is causally involved in social transmission of fear in pups, PND 11-13 pups were bilaterally implanted with intra-LBA amygdala cannulae and 2-3 d later (14) had the amygdala suppressed (using GABA A receptor agonist muscimol) or received vehicle (control) infusion followed by the social transmission of fear procedure.…”
Section: Amygdala Inactivation Prevents Mother-to-infant Transfer Of supporting
confidence: 64%
“…Our data show robust infant amygdala activation during the social transmission of fear (2-DG, c-Fos) consistent with adult social fear learning data (18,25). To determine if the amygdala is causally involved in social transmission of fear in pups, PND 11-13 pups were bilaterally implanted with intra-LBA amygdala cannulae and 2-3 d later (14) had the amygdala suppressed (using GABA A receptor agonist muscimol) or received vehicle (control) infusion followed by the social transmission of fear procedure.…”
Section: Amygdala Inactivation Prevents Mother-to-infant Transfer Of supporting
confidence: 64%
“…The former is in contrast to several studies showing no age-dependent differences in basal c-Fos expression [5,13,28,34,36,42]. This discrepancy might be explained by very recent results obtained by Knapska et al [22]. They showed that structures involved in higher processing of emotional stimuli can be activated by between-subject transfer of information (for example by ultrasound vocalisation or odours [22]).…”
Section: Discussioncontrasting
confidence: 53%
“…This discrepancy might be explained by very recent results obtained by Knapska et al [22]. They showed that structures involved in higher processing of emotional stimuli can be activated by between-subject transfer of information (for example by ultrasound vocalisation or odours [22]). In our experiment rats were housed in groups of two to three per cage and the cages were located close to each other in one experimental room.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Translational rodent models that capture aspects of social affective cognition include emotion contagion [50][51][52][53] , social buffering 41 and even helping 54,55 (for review of models see 56 ). However, interpreting the underlying cognitive mechanisms is challenging because some paradigms involve repeated conditioning, direct exposure to a conspecific in pain or receiving aversive stimulation [57][58][59][60] , making it difficult to rule out self-serving or socially rewarding motives 41,61 .…”
mentioning
confidence: 99%